SISTEM INFORMASI MONITORING KEGIATAN ABSENSI SISWA DENGAN NOTIFIKASI WHATSAPP - Dedi Jubaedi, Ahmad; Dwiyatno, Saleh; Krisnaningsih, Erni; Solihin; Shafitri, Adhe; Sutiawan , Ade (Universitas Serang Raya, 2023)
This study focuses on Student Attendance Monitoring Information Systems with WhatsApp Notifications using the Waterfall method. Is a system designed to assist teachers and parents in monitoring student attendance effectively and in real-time. This system will send notifications via the WhatsApp application every time there is a lesson. Because there is still cheating or errors on the part of both students and teachers who are wrong in marking student attendance and the use of conventional attendance systems that are inefficient in terms of managing and controlling student attendance data. The Waterfall method was chosen because it is in accordance with a structured and gradual system development process. This method involves stages such as planning, analysis, design, implementation, and testing. In the planning stage will determine the needs and specifications of the system. The analysis phase will evaluate requirements and specifications to ensure that the system meets user requirements. The design phase will determine how the system will look and function. The implementation phase will execute the design and build the actual system. The testing phase will ensure that the system functions properly and meets specifications. From the results of the research, a Student Absenteeism Monitoring Information System with WhatsApp Notifications was created using the Waterfall method which can assist teachers and parents in monitoring student attendance effectively and in real-time. This system will simplify communication and make more informed and accurate decisions. This system can help in increasing student attendance, helping teachers and parents to work together in minimizing student absence.